In vitro antioxidant, PTP-1B inhibitory effects and in vivo hypoglycemic potential of selected medicinal plants - Arya, A.; Looi, C.Y.; Wong, W.F.; Noordin, M.I.; Nyamathulla, S.; Mustafa, Mohd Rais; Mohd, M. Ali (2013)
The therapeutic potential of plants varies according to their parts. The present study was aimed to ascertain the antioxidant and antidiabetic potential of crude fractions obtained from different parts of 6 medicinal plants, Centratherum anthelminticum, Cissus quadrangularis, Terminalia bellerica, Terminalia chebula, Terminalia arjuna and Woodfordia fruticosa. Total phenolic (TPC), total flavonoid (TFC) and total tannin content (TTC) were determined. In vitro antioxidant abilities were showed by 1, 1-diphenyl-2-picrylhydrazyl (DPPH), Oxygen Radical Absorbance Capacity (ORAC) and Ferric Reducing/antioxidant Power (FRAP) assays. Furthermore, anti-diabetic potential was determined using in vitro protein tyrosine phosphatase-1B (PTP-1B) inhibition assay and blood glucose lowering effects were evaluated on streptozotocin (STZ)-induced diabetic rats. The result of our study showed that T. chebula fruit exhibited highest amount of TPC (910.43±37.45 mg GAE g-1) and TTC (65.6±6.83 mg Catechin g-1), respectively. Whereas C. anthelminticum seeds contained highest amount of TFC (98.2±27.6 mg Quercetin g-1). The free radical scavenging capacity of T. chebula fruits was the highest among the six plants as determined by DPPH (3.6±0.13 μg mL-1) and FRAP (109.6±2.5 μg mL-1) assays. C. anthelminticum seeds (9.16±0.62 μM mL-1) demonstrated highest oxygen radical absorbance capacity in ORAC test. In addition, C. anthelminticum seeds (38±5.8 μM) showed highest PTP-1B inhibitory effects and maximum blood glucose lowering effects in STZ-induced diabetic rats. Altogether, our findings suggest that T. chebula fruit is potent in ameliorating oxidative damage whereas, C. anthelminticum seeds possess highest antidiabetic and antioxidant properties.